1996
DOI: 10.2307/2061709
|View full text |Cite
|
Sign up to set email alerts
|

Community and contraceptive choice in rural Thailand: A case study of Nang Rong

Abstract: This paper blends quantitative with qualitative data in an investigation of community and contraceptive choice in Nang Rong, Thailand. Specifically, it develops an explanation of 1) method dominance within villages, coupled with 2) marked differences between villages in the popularity of particular methods. The quantitative analysis demonstrates the importance of village location and placement of family planning services for patterns of contraceptive choice. The qualitative data provide a complementary perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(109 citation statements)
references
References 12 publications
5
103
0
1
Order By: Relevance
“…Women whose health service provider offered these services had rates of contraceptive use to stop childbearing 171 and 87 percent higher, respectively. These findings are as we would expect given previous experimental and observation studies on the effects of family planning services on contraceptive use (Entwisle et al 1996;Freedman and Takeshita 1969;Koenig et al 1987).…”
Section: Family Planning Servicessupporting
confidence: 86%
See 1 more Smart Citation
“…Women whose health service provider offered these services had rates of contraceptive use to stop childbearing 171 and 87 percent higher, respectively. These findings are as we would expect given previous experimental and observation studies on the effects of family planning services on contraceptive use (Entwisle et al 1996;Freedman and Takeshita 1969;Koenig et al 1987).…”
Section: Family Planning Servicessupporting
confidence: 86%
“…Extensive evidence demonstrates that organized family planning programs have substantial influence on couples' childbearing behavior, particularly in terms of contraceptive use and choice of effective methods (Angeles, Guilkey and Mroz 1998;Entwisle et al 1996;Freedman and Takeshita 1969). The spread of and improvement in family planning services directly address the inadequate access to services that women in poor, rural settings face (Buor 2003;Casterline and Sinding 2000;Hermalin and Entwisle 1987).…”
Section: Family Planning Servicesmentioning
confidence: 99%
“…This result is consistent with a large body of both statistical and qualitative evidence of the importance of social influences on contraceptive decisions (Rutenberg and Watkins 1997; Montgomery and Casterline 1993; Montgomery and Chung 1999; Entwisle et al. 1996). The power of social influence goes a long way towards explaining why the range of methods used in most populations is so narrow.…”
Section: Discussionmentioning
confidence: 99%
“…For example, demographers have found that the attitudes and behaviors of an individual are strongly related to the presence of these same attitudes and behaviors among those with whom she interacts (e.g. Montgomery and Casterline 1993;Entwisle et al 1996;Valente et al 1997;Munshi and Myaux 1997;Montgomery and Chung 1999;Entwisle and Godley 1998;Kohler, Behrman and Watkins 2001;Behrman, Kohler and Watkins 2002;Bühler and Kohler 2003), and similar analyses have been conducted with respect to more general behaviors (e.g. Brock and Durlauf 2001).…”
Section: Introductionmentioning
confidence: 91%